2020
DOI: 10.2174/0929867326666190227232721
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Glyco-Macrocycles: Potential New Lead and their Future in Medicinal Chemistry

Abstract: Macrocycles cover a small segment of molecules with a vast range of biological activity in the chemotherapeutic world. Primarily, the natural sources derived from macrocyclic drug candidates with a wide range of biological activities are known. Further evolutions of the medicinal chemistry towards macrocycle-based chemotherapeutics involve the functionalization of the natural product by hemisynthesis. More recently, macrocycles based on carbohydrates have evolved a considerable interest among the medicinal che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 153 publications
0
18
0
Order By: Relevance
“…[71][72][73] Different strategies were further employed in the construction of fullerene-containing pillar[n]arene hybrid composites/ Scheme 5 Schematic illustration of the formation of PF2 . Z3 by PF2 and Z3, as well as the fabrication of [2]rotaxane PF2 . Z5 with the reaction with Z4.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[71][72][73] Different strategies were further employed in the construction of fullerene-containing pillar[n]arene hybrid composites/ Scheme 5 Schematic illustration of the formation of PF2 . Z3 by PF2 and Z3, as well as the fabrication of [2]rotaxane PF2 . Z5 with the reaction with Z4.…”
Section: Reviewmentioning
confidence: 99%
“…As a significant rising star in macrocycle chemistry, [1][2][3][4][5][6][7][8] the short rigid cylindrical structure of pillar[n]arenes (Scheme 1) 9,10 resembles the molecular architecture of carbon nanotubes, [11][12][13] and provides the possibility of introducing unique planar chirality [14][15][16] by functionalizing larger alkyl and aromatic groups. [17][18][19] In fact, pillar[n]arene could perform as an efficient structural basis for the synthesis of one-dimensional (1D) linear tubular structures, [20][21][22][23][24] and serve as an interesting additive for improving the physiochemical properties of another significant two-dimensional (2D) carbon material, graphene, [25][26][27] for example, to diversify applications in biomedicine and electrochemical sensor devices.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity and specificity offered by sugar units make it an ideal class of compounds for the development of novel therapeutic agents. , Previously explored carbohydrate moieties found in glycoside-based antimicrobial drugs (AMDs) and other potentially active molecules were mainly believed to enhance their pharmacokinetics (PK) properties, such as solubility, bioavailability, transportation, and toxicity modulation. Studies have shown that for numerous AMDs, the carbohydrate residue is involved in carbohydrate–protein interactions and carbohydrate–DNA and RNA interactions. , The knowledge of cell-to-cell recognition and an improved understanding of the pathophysiological importance of carbohydrate–protein interactions have led to the resurgence of molecular level studies of carbohydrate-based active pharmaceuticals and glycomimetics .…”
Section: Introductionmentioning
confidence: 99%
“…Macrocyclic compounds are important classes of molecules with many biological applications and useful for drug discovery [ 1 , 2 ]. Carbohydrate-based macrocyclic compounds have unique molecular architectures and many practical applications [ 3 , 4 ]. Naturally existing and synthetic carbohydrate-based macrocycles have been utilized in drug discovery, molecular recognition, and as advanced functional materials [ 1 , 3 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%